2003
DOI: 10.1002/cncr.11385
|View full text |Cite
|
Sign up to set email alerts
|

Results of a 2‐arm Phase II study of 9‐nitrocamptothecin in patients with advanced soft‐tissue sarcomas

Abstract: BACKGROUNDThe authors conducted a 2‐arm Phase II trial of 9‐nitrocamptothecin (9‐NC), an oral topoisomerase I inhibitor, to define response rates in patients with gastrointestinal (GI) leiomyosarcomas and other soft‐tissue sarcomas (STS).METHODSPatients were required to provide informed consent and have measurable disease, Zubrod performance status ≤ 2, and adequate organ function. 9‐NC was administered orally at 1.5 mg/m2 per day × 5 days every week. Response evaluation was performed at 8 weeks, and those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Three patients (with malignant fibrous histiocytoma [MFH], extraskeletal Ewing's and extraskeletal chondrosarcoma), out of a total of 39, achieved a PR for a response rate of 9%. Toxicities included diarrhoea, fatigue, anorexia, nausea, vomiting and myelosuppression, which were manageable [21]. In another study of 9-NC at a dose of 1.25 mg/m 2 o.d.…”
Section: -Nitrocamptothecinmentioning
confidence: 96%
“…Three patients (with malignant fibrous histiocytoma [MFH], extraskeletal Ewing's and extraskeletal chondrosarcoma), out of a total of 39, achieved a PR for a response rate of 9%. Toxicities included diarrhoea, fatigue, anorexia, nausea, vomiting and myelosuppression, which were manageable [21]. In another study of 9-NC at a dose of 1.25 mg/m 2 o.d.…”
Section: -Nitrocamptothecinmentioning
confidence: 96%
“…Phase 1 Studies in Patients with Solid Tumors Rubitecan has been evaluated in numerous phase 1 studies, with different formulations, in solid tumors and leukemia [18]. In a study in solid tumors, in patients treated with 1, 1.5, or 2 mg/m 2 /day for 5 days followed by 2 days of rest, the DLT was hematologic, gastrointestinal AEs were the next most significant AEs, and the RP2D was 1.5 mg/m 2 /day for 5 days each week [52].…”
Section: Rubitecanmentioning
confidence: 99%
“…Given the encouraging response rates mentioned above and the tive of the plant alkaloid camptothecin, was shown to be effective fact that remissions are comparably durable, [49,54] trabectedin is an in STS, inducing partial responses in 3 of 39 patients with different attractive substance with potential activity in combination chemo-STS histologies (response rate 8% [CI 95% 0, 16]). [71] Topotecan, therapy regimens. Brostallicin is also currently being investigated another DNA topoisomerase I inhibitor, has been evaluated and versus doxorubicin in a randomized EORTC STBSG phase II trial found to be ineffective in pretreated STS.…”
Section: Anthracyclines With or Without Ifosfamidementioning
confidence: 99%